Review on Solid lipid nanoparticles - Parasakthi, N.; PalanisamyP, PalanisamyP (Journal of Neonatal Surgery, 2025)
Noble drug administration and traditional drug distribution have both failed to enhance medication bioavailability and mitigate drug toxicity. In recent years, tailored drug delivery systems have become significant for administering medications with less toxicity and enhanced bioavailability. Nanotechnology has revolutionized medicinal delivery. Solid lipid nanoparticles (SLNs) have demonstrated efficacy as superior medication carriers. SLNs possess several uses in the prevention of cancer and tuberculosis, and they serve as adjuvants in different vaccinations. The preparation procedures for solid lipid nanoparticles (SLNs) encompass homogenization under pressure, ultrasonication, and solvent evaporation, and are contingent upon the characteristics of the medication. The biodistribution of pharmaceuticals is a difficulty, effectively addressed by selecting the optimal route of administration. The characterization of drugs is crucial for solid lipid nanoparticles (SLNs) to enhance drug bioavailability, encompassing several techniques such as electron microscopy, particle size analysis, and zeta potential measurement.